Approach to the diagnosis and management of snakebite envenomation in South Africa in humans. - T Hardcastle; A Engelbrecht; V Lalloo; C Bell; M Toubkin (South African Medical Journal, 2023)
Snake bite management is largely driven by expert opinion and consensus, however there are a few large retrospective studies and RCT’s that have improved the quality of medical guidance currently available. South African snakes are different in the venomous potential and it behooves the hospital provider and the average medical practitioner to know the current best practice concepts concerning assessment, treatment and antivenom use. The recent SASS meeting in July 2022 provided an update and national consensus from which this Hospital Care document is derived.